Analysis of Students' Creative Thinking in Solving Cuboid Problems - Anisah Saida; Muhammad Ikram; Salwah (International Journal of Progressive Mathematics Education, 2021)
Background. The block problem in this study is the main part of the creative thinking instrument designed as an open-ended task that stimulates students to think creatively which will be analyzed based on the category of creative thinking. The research aims to analyze students' creative thinking in solving block problems. Based on the results of the study, 3 aspects of creative thinking categories will be analyzed, namely fluency, flexibility, and originality. This research was conducted in Junior High School with subject criteria that could solve open-ended problems. The research method used qualitative by giving open-ended assignments accompanied by think-aloud and interview guidelines. Data analysis used descriptive analysis in accordance with qualitative research with triangulation of methods, and theories. The results showed that there were 3 subjects selected based on the completeness of the data from the think-aloud, interviews, and work results so that S1 was determined as the subject of the fluency category, S2 as the subject of the flexibility category, and S3 as the subject of the originality category. Based on the results of the study, the subject of fluency solved the problem in a short time then the answers produced varied, but with the same strategy, the subject of flexibility found various answers with various strategies, and the subject of originality produced answers that were different and unique from other subjects. Â  Latar belakang. Blok soal dalam penelitian ini merupakan bagian utama dari instrumen berpikir kreatif yang dirancang sebagai tugas terbuka yang merangsang siswa berpikir kreatif yang akan dianalisis berdasarkan kategori berpikir kreatif. Penelitian bertujuan untuk menganalisis pemikiran kreatif siswa dalam memecahkan masalah balok. Berdasarkan hasil penelitian akan dianalisis 3 aspek kategori berpikir kreatif yaitu kelancaran, fleksibilitas, dan orisinalitas. Penelitian ini dilakukan di Sekolah Menengah Pertama dengan kriteria mata pelajaran yang mampu menyelesaikan masalah open-ended. Metode penelitian yang digunakan kualitatif dengan memberikan tugas terbuka disertai pedoman berpikir keras dan wawancara. Analisis data menggunakan analisis deskriptif sesuai dengan penelitian kualitatif dengan triangulasi metode, dan teori. Hasil penelitian menunjukkan terdapat 3 subjek yang dipilih berdasarkan kelengkapan data hasil think-aloud, wawancara, dan kerja sehingga S1 ditetapkan sebagai subjek kategori kelancaran, S2 sebagai subjek kategori fleksibilitas, dan S3 sebagai mata kuliah kategori orisinalitas. Berdasarkan hasil penelitian, subjek kelancaran menyelesaikan soal dalam waktu singkat kemudian jawaban yang dihasilkan bervariasi, namun dengan strategi yang sama, subjek fleksibilitas menemukan jawaban yang beragam dengan berbagai strategi, dan subjek orisinalitas menghasilkan jawaban yang bervariasi. berbeda dan unik dari mata pelajaran lainnya.